ZINC AND SELENIUM INTAKE BY SMALL-FOR-DATE INFANTS DURING BREAST FEEDING - O. A. Senkevich; Z.А. Komarova (Вопросы современной педиатрии)
Optimal nutrition of small-for-date infants is a topical issues for neonatal nutrition. Breast milk is adapted for infant’s uptake, but its components both in quality and quantity sense depends on time of the delivery and differs essentially from normal findings in case of  low birth weight. To solve the problem of dietary intake for small-for-date babies it’s important to determine the components of breast milk. Background: To determine zinc and selenium concentration in the milk of women who gave birth to small-for-date babies, as well as to estimate an actual intake of these microcells, during infants’ breastfeeding. Patients and methods: In 10–14 days after delivery zinc and selenium rate in breast milk of 52 women who gave birth to small-for-date babies, and of 20 healthy, has been estimated by Inductively coupled plasma mass spectrometry (ICP-MS ELAN DRC II, Perkin Elmer, USA). Results: Zinc and selenium concentration is essentially low in the milk of women who gave birth to small-for-date babies which results in baby low supply with microcells, who is breastfed. The analysis results confirm the statement about high risk of development of alimentary-dependent conditions in smallfor-date babies. Conclusion: Correction of microcells concentration in breast milk is possible in case of creating preventive measures system in pre- and postnatal period for their imbalance in pregnant and nursing women. This may favor the effective support of infants with biocells, which is essential for proper nutrition and keeping the children healthy.